Enabling Environment for Agricultural Growth and Competitiveness Evaluation, Indicators and Indices - Diaz-Bonilla, Eugenio (OECD Publishing, 2014)
The key contribution of this report lies in developing a typology to structure the components of the enabling environment for agricultural growth and competitiveness, and in constructing an illustrative Agricultural Growth Enabling Index (AGEI) to summarise a wide array of available information in a coherent manner. The construction of the preliminary AGEI is based on four blocks with 40% of the weight on agriculture/rural factors and 20% each on broader economy-wide governance, capital availability and market operation. The AGEI can be used to provide across-country comparisons or single-country evaluations using the index itself or its components. It allows the decomposition within each main block to show the relative strength and weaknesses of each country across various sub-indices. It has been applied here to a selected set of twenty emerging and developing countries. The preliminary results demonstrate that the AGEI brings together information relevant to the enabling environment for agricultural growth and competitiveness, and which is largely consistent with more in-depth studies of the selected countries. While constrained in some respects, the AGEI appears to be the first index completed with this objective. Further expansion and refinement of the included set of indicators to better reflect key determinants of agriculture's enabling environment would help provide an important input into better policy decisions
Keywords: Agriculture and Food